Penerapan Konseling Islami Berbasis Nilai-Nilai Spiritual Keagamaan - Syamsu Yusuf LN. (STAI Siliwangi Bandung, 2016)
Islamic counseling is a helping process that facilitates individual (counselee) to have awareness and commitment to be “back to religion”, return to humanity nature as a religious being. In the course of this counseling, an individual can reach enlightenment in arranging pattern of life, either the pattern of attitude, thought, and behavior towards wellness personal and social life, peace-spirited (sakinah), mutual love (mawaddah), and excited to build prosperous life (rahmah) together. An individual who have been able to internalize the values of ​​sakinah, mawaddah, and rahmah, will be spared from the atmosphere of mental illness or psychological illness (amraadul quloob), such as individualistic, exploitative (greedy or gluttonous and violence/radical), bourgeoisie, materialistic, and hedonistic (hub-ud-dunyaa wakarahiyat-ul maut), which trigger life catastrophe on this earth.